ANALISIS YURIDIS PEKERJA ANAK DI SEKTOR INFORMAL DI KOTA PALU - Andi Nurul Isnawidiawinarti Achmad (Maleo Law Journal, 2019)
The purpose of this study was to determine the effects of children working in the informal sector in Palu City and legal protection for child labor in the informal sector in Palu City. From the results of the study by the author, it was found that the consequences arising from children working in the informal sector mostly impacted on the education of child workers. Where most of the children who work in the informal sector in the city of Palu experienced dropouts. In terms of legal protection, it appears that legal protection for child labor in the informal sector is inadequate, it can even be said to be neglected both in terms of civil service and in terms of criminal law. Therefore it is expected that the government will issue legislation prohibiting anyone from employing children in the informal sector.  Keyword: child labor, legal protection, informal sector